Biochemical and Histopathology Analysis of Liver Damage in Hypercholesterolemic Rats Induced by Tomato Extract - Retno Sri Iswari; Muchamad Dafip; Muhammad Rifa'i (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2020)
Hypercholesterolemia is a condition caused by high cholesterol consumption. Tomatoes is well known has cholesterol-lowering effects. However, high consumption of tomato shall be concerned especially prooxidant potential that may damage the organ, especially in liver. This study aims to understand the effect of hypercholesterolemic and tomato administration to the rat’s liver, which is monitored using aspartate transaminase (AST), alanine transaminase (ALT) and histological condition. A total 24 of 12-weeks-old male-rats divided into 4 groups, equally. The K1 as normal group consist of placebo-treatment rats; K2 group as hypercholesterolemia group induced with high-cholesterol diet and 2 ml of cholesterol; K3 group was hypercholesterolemia rats treated with 20 mg of atorvastatin; and the last is K4 group was cholesterol rats supplemented with 16 mg/ day of tomato extract. All samples were treated for 60 days. The highest levels of AST and ALT level was 76.39 U/L and 45.40 U/L, respectively, was found in K2. Then, K4 is not significantly different from K3 and K1 and significantly different from K2. The scoring results showed that all groups experienced damage in the form of parenchymal degeneration, fat degeneration and necrosis. From this study it can be concluded that tomato extract gives a protection to the liver from cholesterol-oxidation damage effect. The updating information about how tomato inhibite liver fattening. The liver condition probably can be considered as biomarker-related hypercholesterolemia and developed a diagnostic marker to prevent increases metabolic disorder in community.